Incentive and their role in promoting human resource - dehikel, Ameur; bebsebaa, Abdelkader (Social Empowerment Journal, 2021)
This research aims at studying the topic of incentives and their role in promoting and developing the human resources in order to identify the different forms and types of incentives used inside the university, and its impact on the professional performance of the employees. The incentives system is one of the strategies that has proved its success according to many studies. These studies are based on the descriptive method, and on questionnaire directed to a random sample composed of 196 university professors. The main results has shown that material and moral incentives play a major role in promoting human resources and the quality of performance.